The role of environmental factors in the etiology of schizophrenia - Brzuszkiewicz, Kinga; Rudziński, Gracjan; Łozowski, Borys; Raczkiewicz, Przemysław; Kusak, Natalia; Soroka, Ewelina (Journal of Education, Health and Sport, 2023)
Introduction: Schizophrenia is a psychotic disease characterized by multifaceted psychopathology. To date, research has shown that it is an inherited disease and significant progress has been made in identifying genetic risk factors. Methods: This paper summarizes the current and most recent findings on the role of environmental factors, and demonstrates the continued need for more in-depth research to better understand how this type of disorder occurs. Results: Recent studies show that 15-40% of the risk that comes from environmental sources is not fully understood. Environmental factors that have been repeatedly studied and have been proven to influence the development of the disease include: obstetric complications, infections, childbirth in the winter or spring month, living in the city, severe childhood events or marijuana use. Discussion: Schizophrenia is a devastating mental illness that remains poorly understood. A full picture of how genetic and environmental risk factors affect the risk of developing schizophrenia requires an understanding of the interactions between them. It should be taken into account that for this disorder, the interactions between genetic and environmental risk factors are also not well understood and deserve further research in the future. In the case of schizophrenia, the interactions between environmental and genetic risk factors are not well understood and still require further research. Elucidating the mechanisms underlying the disease is extremely important, as it may have an impact on taking measures to prevent the development of the disorder. In addition, their discovery will help improve treatment. In conclusion, it is important to emphasize the need for further research to better understand the impact of environmental factors on the development of susceptibility to a mental disorder such as schizophrenia.